O ensino de História na educação de jovens e adultos: a construção do currículo e o fazer docente no município de Santo André - Cunha, Andre Luiz Lirio Da [UNIFESP] (2019)
This dissertation aims to analyze the teaching of History in the education of young people and adults in the context of curricular construction in the municipal network of Santo André, in the period between 2013 and 2016. The objective of this work is to investigate the forms of participation of teachers in the process of curricular construction to understand how the teachers' performance in the pedagogical discussions and formations in the process developed and how this experience intervened (or not) in their teaching practices in History teaching, as well as the principles related to youth and adult education. We base ourselves on the theoretical assumptions of Ivor Goodson's (1995) social construction of the curriculum, articulating them with the conceptions of popular education Paulo Freire (1983, 1996) and the experience category of EP Thompson (1981, 2002), which considers the subjects as reflective and active in their own history, even with obvious limitations. From the documentation produced in the period and the semi-structured interviews with two teachers of History of the EJA of Santo André. Thus, as a propositional part of the dissertation, a material with elaborated activities was constructed using as a starting point the social practice, that is, the educator individually and collectively from their social experiences mediated by the socially constructed knowledge.